Confabulations Related to Tacit Awareness in Visual Neglect - L. Manning; L. D. Kartsounis (Behavioural Neurology)
The case of a man with left-sided visuospatial neglect is reported. His performance on a test for neglect, the “burning house test”, is analysed and compared with that of other patients referred to in the literature. We suggest that the confabulations neglect patients may produce when confronted with this test reflect the degree of preconscious awareness for left-sided features.